PAIR as a Treatment Option for Isolated Intramuscular Cysticercosis: A Case Report - Shailendra Singh Naik; Nisha Das; Shraddha Modi; Tirou Aroul (Journal of Clinical Interventional Radiology ISVIR)
Cysticercosis is a parasitic disease caused by Taenia solium. Central nervous system is the most common site of infestation. Other organs infested are subcutaneous tissue, eye, muscle, liver, and lung. Cysticercosis in muscle can occur in three forms: myalgic type, mass-like pseudotumor, and rarely pseudohypertrophic type. Solitary cysticercosis of muscle without involvement of the central nervous system is rare. In this case report, percutaneous-aspiration-injection-reaspiration (PAIR) has been used as a treatment option for isolated intramuscular cysticercosis of the anterior abdominal wall. Interventional radiological management along with medical management was done to observe complete resolution of the cyst.